A method for improving the dephosphorization capacity in the early stage of converter blowing
By adding surfactant and steel slag emulsifier in the pre-blowing stage of converter blowing, the emulsification capacity and dephosphorization reaction efficiency of steel slag are improved, and the problem of low dephosphorization rate in the early stage of converter blowing is solved, and efficient phosphorus removal and production efficiency are achieved.
Patent Information
- Application Number
- CN202310630690.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-05-31
AI Technical Summary
In the prior art, the dephosphorization rate of converter blowing is low and the time is long, which makes it difficult for the phosphorus content in steel to reach the requirement of less than 0.01%.
By adding slag-making materials containing surfactant in the slag-making stage before blowing, and continuously adding steel slag emulsifier during blowing, the oxygen gun flow and height are controlled, and the slag alkalinity and FeO content are adjusted to improve the emulsification ability of the steel slag and the dephosphorization reaction efficiency.
The dephosphorization rate of the converter blowing pre-stage is significantly improved, making it reach more than 75%, while shortening the converter smelting cycle and improving production efficiency.
Smart Images

Figure GHA0000010044280000041 
Figure GHA0000010044280000042 
Figure GHA0000010044280000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of converter steelmaking, and more particularly to a method for improving the dephosphorization capacity in the early stage of converter blowing. Background Art
[0002] Phosphorus is the main impurity element in steel, which can cause a series of problems such as "cold brittleness" and reduced low-temperature toughness of steel. Therefore, high-quality steel generally has strict requirements on the phosphorus content in steel. For example, some low-temperature steel, marine steel, hydrogen-resistant cracking steel, some thick plate steel, natural gas and oil pipeline steel require the phosphorus content in steel to be less than 0.01%, or even less than 0.003%. At present, there are three main dephosphorization methods at home and abroad:
[0003] The first is a molten iron pretreatment dephosphorization method, such as Japanese patent JPS62109908A. This method mainly involves pre-dephosphorizing the desiliconized molten iron in a torpedo car or a ladle. Due to the poor power conditions for dephosphorization in a torpedo car or a ladle, the dephosphorization rate is relatively low, the molten iron temperature drops significantly, and the scrap steel ratio is low.
[0004] The second is a double dephosphorization method in a converter. This method is mainly to overcome the problem of poor kinetic conditions in the pretreatment dephosphorization of molten iron. The dephosphorization treatment container is transferred from a torpedo tank car or a ladle to a converter, and two converters are used for smelting. One converter is used for dephosphorization, and after dephosphorization, the decarburization is carried out in another converter, such as Japanese patent JPS63195210A. Although this method realizes the production of low-phosphorus steel, it is necessary to pour molten iron from one converter into another converter, resulting in a large heat loss, and an additional dephosphorization converter is required, which increases investment and prolongs the production process. This method is only used in a few domestic steel companies, such as Shougang (see patent CN102443675A).
[0005] The third method is to use the same converter to achieve dephosphorization and decarburization. This method can be divided into two processes according to the difference in slag basicity and slag volume during the dephosphorization period:
[0006] The first is the traditional "double slag method" process (such as Chinese patents CN101906504A, CN102071277A, etc.). In the dephosphorization stage, this process uses multiple high-basicity slag (R>2) and slag removal to achieve the production of low-phosphorus steel. It has the following disadvantages: (1) high basicity is used in the dephosphorization stage, the slag volume is large, and the consumption of raw and auxiliary materials is high; (2) the dephosphorization rate in the dephosphorization stage is not high, generally less than 50%.
[0007] The second is a "double slag + slag retention" smelting process similar to the MURC (Multi-refining Converter) process of Nippon Steel Corporation of Japan. The process flow is: adding scrap steel, adding molten iron → desiliconization and dephosphorization in converter → discharging the early dephosphorization slag → blowing decarburization and heating → converter steelmaking → slag retention. In this process, efficient dephosphorization is one of its key technologies. Domestic steel companies mainly use two methods to improve the dephosphorization rate. One is to extend the dephosphorization stage time, such as the dephosphorization period time of 7 to 10 minutes in Chinese patent CN102618689A; the other is to improve the dephosphorization rate by adjusting the oxygen lance operation and slag property control, such as Chinese patents CN102776314A and CN103243192A. Although this process can reduce steelmaking costs, it has the following disadvantages: (1) the dephosphorization rate in the dephosphorization period is not high, less than 60%; (2) the dephosphorization time is long, which prolongs the converter smelting cycle and increases production costs.
[0008] After searching, patent CN112877496A discloses a method for achieving efficient dephosphorization during the dephosphorization period by controlling the physical phase of the slag forming process. The invention controls the type, size and solid-liquid ratio of the liquid phase (mainly FeO and Ca3Fe2O5) and solid phase (mainly 2CaO·SiO2, 2CaO·SiO2-3CaO·P2O5) during the slag forming process. The size of the 2CaO·SiO2 solid phase is ≤5μm, and the size of the 2CaO·SiO2-3CaO·P2O5 solid phase is ≤50μm. The control method of the invention improves the dephosphorization efficiency during the dephosphorization period to a certain extent, but since the dephosphorization reaction is a steel slag interface reaction, it does not consider the effect of the change in the steel slag interface area on the dephosphorization, so the dephosphorization rate is low and the time is long in the early stage of blowing. Summary of the invention
[0009] 1. Technical problem to be solved by the invention
[0010] The present invention aims at the problem of low dephosphorization rate and long time in the early stage of converter blowing in the prior art, and provides a method for improving the dephosphorization capacity in the early stage of converter blowing. The method can improve the dephosphorization rate in the early stage of converter blowing and improve the production efficiency of the converter.
[0011] 2. Technical solution
[0012] In order to achieve the above object, the technical solution provided by the present invention is:
[0013] Step a, slag retention: after the last furnace is finished tapping, slag is retained, and the amount of slag retained is controlled to be 30-60kg / t steel, and then slag is splashed to solidify the slag;
[0014] Step b. Slag making: Scrap steel is added to the converter, and hot metal is charged. According to the silicon content in the hot metal, the addition of slag-making materials in the early stage of blowing is controlled. The slag-making materials include iron ore, and the addition amount of iron ore is controlled at 0 - 25 kg / t. The slag-making materials also include one or more of lime, limestone, and surfactant. When Si ≤ 0.3%, the addition amount of surfactant is controlled at 2 - 3 kg / t; when 0.3% < Si ≤ 0.6%, the addition amount of lime is controlled at 3 - 5 kg / t, and the addition amount of surfactant is controlled at 1 - 2 kg / t; when 0.6% < Si, the addition amount of lime is controlled at 3 - 5 kg / t, and the addition amount of limestone is controlled at 3 - 8 kg / t. Among them, SiO2 in the slag-making materials is the main active material. According to different silicon contents, the addition amount and type of slag-making materials are adjusted to supplement the silicon content in the hot metal, that is, the more the original silicon content in the hot metal, the more the external silicon source.
[0015] Step c. Blowing: In the first 2 minutes of blowing, the oxygen lance flow rate is controlled at 3.5 - 4 m 3 / min / t, and the oxygen lance height is 2 - 3 m above the molten pool surface; within 2 - 4 minutes of blowing, the oxygen lance flow rate is adjusted to 3.0 - 3.3 m 3 / min / t, the oxygen lance height is adjusted to 1 - 1.5 m above the molten pool surface, and a steel slag emulsifier is continuously added to the converter at a rate of 0.1 - 0.5 kg / t / min to control the degree of steel slag emulsification. In the early stage, for rapid de-siliconization, a large flow rate and high lance position are adopted to increase the content of surface active substances in the slag; in the later stage, to prevent splashing caused by too high stirring intensity, the oxygen flow rate is appropriately reduced. To provide the stirring ability of the molten pool, promote small droplet molten steel to enter the slag, and lower the lance position.
[0016] Step d. Slag discharging: Slag discharging is carried out at 4 - 5 minutes of blowing, and the slag discharging rate is controlled at 50% - 60%;
[0017] Step e. Blowing for decarburization: After slag discharging, blowing for decarburization is carried out. The oxygen supply intensity during the decarburization period is controlled at 3.3 - 3.8 Nm 3 / min / ton of steel, the addition amount of lime is 10 - 30 kg / t, the binary basicity of the decarburization slag in the converter is adjusted to 2.5 - 4.0, the MgO content in the slag is 7 - 10%, and after the converter blowing is completed, tapping and slag retention are carried out to ensure that the slag can meet the requirements of slag splashing for furnace protection and at the same time has good dephosphorization ability.
[0018] Preferably, in the early stage of converter blowing, the binary basicity of the slag is controlled at 1.2 - 2.0, the FeO content is controlled at 8% - 25%, and the MgO content is controlled at 4% - 6%. Controlling the slag within this range can provide good thermodynamic conditions for phosphorus removal, and the appropriate slag viscosity is conducive to subsequent slag discharge. Among them, FeO is a surface-active substance, and an appropriate amount can improve the emulsification ability of the slag. To keep the slag basicity CaO / SiO2 within the target range of 1.2 - 2.0, the lime addition amount is adjusted according to the change in silicon content; when Si > 0.6%, the heat release is large in a short time, and limestone and iron ore can be used to play a cooling role. In addition, using part of limestone to replace lime can also accelerate dissolution.
[0019] Preferably, the mass percentage of the surfactant is: 15% - 25% Cr2O3, 10% - 20% Al2O3, 5% - 10% SiO2, 30% - 40% CaO, and the rest are impurity components. The particle size of the surfactant is 10 - 50 mm. Al2O3 and SiO2 are surface-active substances, which can improve the emulsification ability of the slag; Cr2O3 is an amphoteric substance, playing a regulating role; CaO is used to adjust the melting point of the surfactant and is not easily combined with CaO. It exists at the interface, improving the emulsification ability. Al2O3 can increase the liquid phase content in the slag, promote the contact ratio of phosphorus with the liquid slag phase, and control the reasonable ratio of the surfactant to ensure that the steel slag has reasonable viscosity and emulsification performance during the slag-making stage.
[0020] Preferably, the main component of the steel slag emulsifier is (Mg, Fe)O, the particle size of the steel slag emulsifier is ≤100 nm, and the steel slag emulsifier is sprayed into the molten bath as a solid-phase powder through an oxygen lance. When adding the steel slag emulsifier, the molten bath temperature is 1350 - 1400 °C, and the steel slag emulsification degree is controlled at 50% - 80%. The steel slag emulsification degree is evaluated by the weight percentage of fine iron particles in the steel slag. Among them, (Mg, Fe)O is a solid solution, and the molar ratio of Mg to Fe is 1:1. The steel slag emulsifier still presents a solid phase when added to the molten bath. The nano-scale high-melting-point substance can exist between the interfaces of the emulsified steel slag, increasing the residence time of liquid iron beads and ensuring the time required for the dephosphorization reaction. The continuous high temperature at the interface between the steel slag and the iron beads is conducive to controlling the steel slag emulsification degree, thereby increasing the steel slag interface reaction area, promoting the melting and emulsification of the steel slag, and accelerating the progress of the dephosphorization reaction. If the steel slag emulsification degree is too low, it is not conducive to the dephosphorization reaction.
[0021] In the present invention, by adding a slag-making material containing a surfactant during the slag-making stage before blowing, the surface activity of the steel slag is improved by adding the surfactant. The surface-active substance easily exists between the iron beads and the steel interface, and the emulsification ability of the steel slag is improved through electrostatic action. Further, by adding a steel slag emulsifier, the steel slag emulsifier exists at the interface through chemical adsorption, further improving the emulsification ability of the steel slag, increasing the steel slag interface reaction area, and improving the dephosphorization rate in the early stage of converter blowing.
[0022] 3. Beneficial effects
[0023] Compared with the existing known technologies, the technical solution provided by the present invention has the following significant effects:
[0024] The present invention provides a method for improving the dephosphorization capacity in the early stage of converter blowing. By adding a surfactant and a steel slag emulsifier, the dephosphorization rate in the early stage of converter blowing is significantly improved, so that the dephosphorization rate in the early stage of converter blowing is increased to more than 75%, while shortening the converter smelting cycle and improving the converter production efficiency. DETAILED DESCRIPTION
[0025] The following detailed description of exemplary embodiments of the present invention, although these exemplary embodiments are described in sufficient detail to enable those skilled in the art to implement the present invention, it should be understood that other embodiments may be implemented and various changes may be made to the present invention without departing from the spirit and scope of the present invention. The following more detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but is merely for illustration and does not limit the description of the features and characteristics of the present invention, in order to propose the best way to perform the present invention, and is sufficient to enable those skilled in the art to implement the present invention. Therefore, the scope of the present invention is limited only by the appended claims.
[0026] Among them, Table 1 is the parameters of metal materials in the converter smelting furnace, Table 2 is the slag making and blowing component parameters in the early stage of converter blowing, Table 3 is the component parameters of surfactants, Table 4 is the slag and molten iron parameters in the early stage of converter blowing, and Table 5 is the blowing decarburization process parameters.
[0027] Table 1 Parameters of metal materials in converter smelting heats
[0028]
[0029] Table 2 Parameters of slag making and blowing components in the early stage of converter blowing
[0030] Heat Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Si content, wt% 0.25 0.43 0.56 0.74 0.48 Lime addition amount, kg / t 0 3.3 4.5 4.8 8.2 Limestone addition amount, kg / t 0 0 0 6.3 0 Ore addition amount, kg / t 8.5 9.7 15.6 12.4 11.5 Surfactant addition amount, kg / t 2 1.5 1 0 0 Slag emulsifier addition rate, kg / t / min 0.3 0.5 0.3 0.2 0 Emulsification degree of steel slag, % 71.3 56.4 75.6 63.9 -
[0031] Table 3 Component parameters of surfactants
[0032]
[0033]
[0034] Table 4 Parameters of slag and molten iron in the early stage of converter blowing
[0035]
[0036] Table 5 Blowing decarburization process parameters
[0037]
[0038] Example 1
[0039] This test was carried out on a 150t converter, using the "double slag + slag retention" smelting process for converter smelting, which specifically includes the following steps:
[0040] Step a, slag retention: after the last batch of steel is tapped from the converter, slag retention is performed, and the slag retention amount is controlled to be 50 kg / t. Then, nitrogen is blown to splash the slag to fully solidify the slag.
[0041] Step b, slag making: adding scrap steel and molten iron into the converter, and controlling the weight percentages of molten iron and scrap steel to be 92.1% and 7.9% respectively, according to Table 1, the silicon content in the molten iron is Si≤0.3%, no lime is added, 2kg / t of surfactant is added, the average size of the surfactant is 30mm, and the amount of iron ore added is 8.5kg / t, as shown in Tables 2 and 3.
[0042] Step c, blowing: 2 minutes before converter blowing, control the oxygen lance flow rate to 3.8m 3 / min / t, the oxygen lance height is 2.5m above the molten pool liquid surface to achieve rapid oxidation of silicon in molten iron; within 2-4min of blowing, adjust the oxygen blowing intensity and adjust the oxygen lance flow rate to 3.0m 3 / min / t, the oxygen lance height is lowered to 1.3m above the molten pool surface, and slag emulsifier is continuously added to the converter, and the addition rate is controlled to be 0.3kg / t / min; the slag basicity in the early stage of converter blowing is controlled to be 1.5, the FeO content is controlled to be 12.6%, the MgO content is controlled to be 4.2%, and the slag emulsifier is ≤100nm, so that the emulsification degree of the slag is 71.3%. The specific parameters are shown in Table 4.
[0043] Step d, slag removal: slag removal is performed after blowing for 4.1 min, and the molten pool temperature is controlled at 1385° C. and the slag removal rate is 55%.
[0044] Step e, blowing and decarburization: After the slag removal, blowing and decarburization are carried out, and the oxygen supply intensity during the decarburization period is controlled at 3.5Nm 3 / min / ton of steel, the amount of lime added is 23.4kg / t, the binary basicity of the converter decarbonization slag is adjusted to 3.5, the MgO content in the slag is 8.3%, and the steel is tapped and the slag is retained after the converter blowing is completed. The specific smelting indicators are shown in Table 5.
[0045] Example 1 Compared with the existing "double slag + slag retention" process, its advantages are mainly reflected in not only significantly improving the dephosphorization rate in the early stage of converter blowing and reducing the end-point phosphorus content, but also reducing the lime consumption and the degree of molten steel peroxidation, improving the quality stability of steel. Among them, the total lime addition amount decreased from 29.8 kg / t to 23.4 kg / t, the dephosphorization rate in the early stage of blowing increased from 58.33% to 76.69%, the end-point phosphorus content decreased from 0.014% to 0.008%, and the end-point carbon content increased from 0.043% to 0.075%.
[0046] Example 2
[0047] This test was carried out on a 150t converter, and the "double slag + slag retention" smelting process was used for converter smelting, which specifically included the following steps:
[0048] Step a, slag retention: After the previous heat of the converter was tapped, the slag retention operation was carried out, and the slag retention amount was controlled at 56 kg / t. Then, nitrogen was blown for slag splashing to fully solidify the slag.
[0049] Step b, slag making: Scrap steel was added to the converter, and hot metal was charged. The weight percentages of hot metal and scrap steel were controlled at 87.6% and 12.4% respectively. According to the silicon content in the hot metal in Table 1 being 0.3 < Si ≤ 0.6%, the lime addition amount was controlled at 3.3 kg / t, 1.5 kg / t of surfactant was added, the average size of the surfactant was 30 mm, and the iron ore addition amount was 9.7 kg / t. See Table 2 for details.
[0050] Step c, blowing: In the first 2 minutes of converter blowing, the oxygen lance flow rate was controlled at 3.7 m 3 / min / t, and the oxygen lance height was 2.4 m above the molten pool surface to achieve rapid oxidation of silicon in the hot metal; within 2 - 4 minutes of blowing, the blowing oxygen intensity was adjusted, the oxygen lance flow rate was adjusted to 3.1 m 3 / min / t, the oxygen lance height dropped to 1.1 m above the molten pool surface, and the steel slag emulsifier was continuously added to the converter at a feeding rate controlled at 0.5 kg / t / min; the basicity of the slag in the early stage of converter blowing was controlled at 1.8, the FeO content was controlled at 15.8%, the MgO content was controlled at 5.6%, and the steel slag emulsifier was ≤ 100 nm, so that the steel slag emulsification degree was 56.4%. See Tables 2 and 3 for specific parameters.
[0051] Step d, slag discharging: Slag discharging was carried out at 4.3 minutes of blowing, and the molten pool temperature was controlled at 1371 °C and the slag discharging rate was 54%.
[0052] Step e, decarburization blowing: After the slag discharging was completed, decarburization blowing was carried out, and the oxygen supply intensity during the decarburization period was controlled at 3.3 Nm 3 / min / ton of steel, the lime addition is 22.4 kg / t, the binary basicity of the converter decarburization slag is adjusted to 3.6, the MgO content in the slag is 8.9%, and after the converter blowing is completed, steel is tapped and slag is retained. The specific smelting indexes are shown in Table 4.
[0053] Compared with the existing "double slag + slag retention" process, the advantages of Example 2 are mainly reflected in not only significantly improving the dephosphorization rate in the early stage of converter blowing and reducing the end-point phosphorus content, but also reducing lime consumption and the degree of overoxidation of molten steel, and improving the quality stability of steel. Among them, the total lime addition amount decreased from 29.8 kg / t to 25.7 kg / t, the dephosphorization rate in the early stage of blowing increased from 58.33% to 79.71%, the end-point phosphorus content decreased from 0.014% to 0.011%, and the end-point carbon content increased from 0.043% to 0.057%.
[0054] Example 3
[0055] This test was carried out on a 150t converter, and the "double slag + slag retention" smelting process was used for converter smelting, which specifically included the following steps:
[0056] Step a, slag retention: After the previous heat of the converter is tapped, the slag retention operation is carried out, and the slag retention amount is controlled to be 60 kg / t. Then, nitrogen is blown for slag splashing to fully solidify the slag.
[0057] Step b, slag making: Scrap steel is added into the converter, and hot metal is charged. The weight percentages of hot metal and scrap steel are controlled to be 83.2% and 16.8% respectively. According to the silicon content in the hot metal of 0.3 < Si ≤ 0.6% in Table 1, the lime addition amount is controlled to be 4.5 kg / t, 1 kg / t of surfactant is added, the average size of the surfactant is 40 mm, and the iron ore addition amount is 15.6 kg / t. See Table 2 for details.
[0058] Step c, blowing: In the first 2 minutes of converter blowing, the oxygen lance flow rate is controlled to be 4.0 m 3 / min / t, and the oxygen lance height is 2.7 m above the molten bath surface to achieve rapid oxidation of silicon in the hot metal; within 2 - 4 minutes of blowing, the blowing oxygen intensity is adjusted, the oxygen lance flow rate is adjusted to 3.2 m 3 / min / t, the oxygen lance height drops to 1.1 m above the molten bath surface, and a steel slag emulsifier is continuously added into the converter at a feeding rate controlled to be 0.3 kg / t / min; the basicity of the slag in the early stage of converter blowing is controlled to be 1.4, the FeO content is controlled to be 10.3%, the MgO content is controlled to be 5.2%, and the steel slag emulsifier ≤ 100 nm, so that the degree of steel slag emulsification is 75.6%. See Tables 2 and 3 for specific parameters.
[0059] Step d, slag discharging: At 4.5 minutes of blowing, slag discharging is carried out, and the molten bath temperature is controlled to be 1363 °C and the slag discharging rate is 58%.
[0060] Step e, blowing for decarburization: After slag discharging, blowing for decarburization is carried out. The oxygen supply intensity during the decarburization period is controlled at 3.7 Nm 3 / min / ton of molten steel, the lime addition amount is 18.2 kg / t, the binary basicity of the converter decarburization slag is regulated to 3.2, the MgO content in the slag is 7.2%, and after the converter blowing is completed, tapping and slag retention are carried out. The specific smelting indexes are shown in Table 4.
[0061] Compared with the existing "double slag + slag retention" process, the advantages of Example 3 are mainly reflected in that not only the dephosphorization rate in the early stage of converter blowing is significantly improved and the end-point phosphorus content is reduced, but also the lime consumption and the degree of overoxidation of molten steel are reduced, and the quality stability of steel is improved. Among them, the total lime addition amount is reduced from 29.8 kg / t to 22.7 kg / t, the dephosphorization rate in the early stage of blowing is increased from 58.33% to 77.71%, the end-point phosphorus content is reduced from 0.014% to 0.009%, and the end-point carbon content is increased from 0.043% to 0.062%.
[0062] Example 4
[0063] This test was carried out on a 150t converter, and the "double slag + slag retention" smelting process was used for converter smelting, which specifically included the following steps:
[0064] Step a, slag retention: After the tapping of the previous converter furnace is completed, the slag retention operation is carried out, and the slag retention amount is controlled at 42 kg / t. Then, nitrogen is blown for slag splashing to fully solidify the furnace slag.
[0065] Step b, slag making: Scrap steel is added into the converter, and hot metal is charged, and the weight percentages of hot metal and scrap steel are controlled at 92.1% and 7.9% respectively. According to the silicon content in the hot metal in Table 1 being 0.3 < Si ≤ 0.6%, the lime addition amount is controlled at 4.8 kg / t, the limestone addition amount is 6.3 kg / t, no surfactant is added, the average size of the surfactant is 45 mm, and the iron ore addition amount is 12.4 kg / t. See Table 2 for details.
[0066] Step c, blowing: In the first 2 minutes of converter blowing, the oxygen lance flow rate is controlled at 3.8 m 3 / min / t, and the oxygen lance height is 2.1 m above the molten bath surface to achieve rapid oxidation of silicon in the hot metal; within 2 - 4 minutes of blowing, the blowing oxygen intensity is adjusted, the oxygen lance flow rate is adjusted to 3.1 m 3 / min / t, the oxygen lance height drops to 1.1 m above the molten bath surface, and a steel slag emulsifier is continuously added into the converter at a feeding rate controlled at 0.2 kg / t / min; the basicity of the furnace slag in the early stage of converter blowing is controlled at 1.2, the FeO content is controlled at 18.6%, the MgO content is controlled at 4.8%, and the steel slag emulsifier ≤ 100 nm, so that the steel slag emulsification degree is 63.9%. See Tables 2 and 3 for specific parameters.
[0067] Step d, slag removal: slag removal is performed after blowing for 4.1 min, and the molten pool temperature is controlled at 1359° C. and the slag removal rate is 51%.
[0068] Step e, blowing and decarburization: After the slag discharge, blowing and decarburization are carried out, and the oxygen supply intensity during the decarburization period is controlled at 3.6Nm 3 / min / ton of steel, the amount of lime added is 21.6kg / t, the binary basicity of the converter decarbonization slag is adjusted to 3.0, the MgO content in the slag is 9.1%, and the steel is tapped and the slag is retained after the converter blowing is completed. The specific smelting indicators are shown in Table 4.
[0069] Compared with the existing "double slag + slag retention" process, the advantages of Example 4 are mainly reflected in that it not only significantly improves the dephosphorization rate in the early stage of converter blowing and reduces the final phosphorus content, but also reduces the lime consumption and the degree of peroxidation of molten steel, and improves the quality stability of steel. The total amount of lime added is reduced from 29.8kg / t to 28.6kg / t, the dephosphorization rate in the early stage of blowing is increased from 58.33% to 81.48%, the final phosphorus content is reduced from 0.014% to 0.010%, and the final carbon content is increased from 0.043% to 0.058%.
[0070] The present invention has been described in detail above in conjunction with specific exemplary embodiments. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description should be considered only as illustrative, not restrictive, and any such modifications and variations, if any, will fall within the scope of the present invention described herein. In addition, the background art is intended to illustrate the current status and significance of the research and development of the present technology and is not intended to limit the present invention or the application field of the present application and the present invention.
[0071] More specifically, although exemplary embodiments of the present invention have been described herein, the present invention is not limited to these embodiments, but includes any and all embodiments that are modified, omitted, combined (e.g., between the various embodiments), adapted and / or replaced as may be recognized by those skilled in the art based on the foregoing detailed description. The limitations in the claims may be interpreted broadly based on the language used in the claims and are not limited to the examples described in the foregoing detailed description or during the implementation of the application, which examples should be considered non-exclusive. For example, in the present invention, the term "preferably" is not exclusive, where it means "preferably, but not limited to". Any steps listed in any method or process claim may be performed in any order and are not limited to the order presented in the claim. Therefore, the scope of the present invention should be determined solely by the appended claims and their legal equivalents, rather than by the description and examples given above.
Claims
1. A method for improving the dephosphorization capacity in the early stage of converter blowing, characterized in that: It includes the following steps: Step a, slag retention: After tapping of the previous heat, retain slag, control the slag retention amount to be 30 - 60 kg / t, and then splash the slag to solidify the slag; Step b, slag making: Add scrap steel into the converter, tap in hot metal, and control the addition of slag-making materials in the early stage of blowing according to the different Si contents in the hot metal. The slag-making materials include iron ore, and the addition amount of iron ore is controlled to be 0 - 25 kg / t. The slag-making materials also include one or more of lime, limestone and surfactant. When Si ≤ 0.3%, the addition amount of surfactant is controlled to be 2 - 3 kg / t; when 0.3% < Si ≤ 0.6%, the addition amount of lime is controlled to be 3 - 5 kg / t, and the addition amount of surfactant is controlled to be 1 - 2 kg / t; when 0.6% < Si, the addition amount of lime is controlled to be 3 - 5 kg / t, and the addition amount of limestone is controlled to be 3 - 8 kg / t. The surfactant includes, by mass percentage: 15% - 25% Cr2O3, 10% - 20% Al2O3, 5% - 10% SiO2, 30% - 40% CaO, and the rest are impurity components; Step c, blowing: Continuously add steel slag emulsifier into the converter within 2 - 4 minutes. The main component of the steel slag emulsifier is (Mg, Fe)O solid solution; Step d, slag discharging: Carry out slag discharging when blowing reaches 4 - 5 minutes, and control the slag discharging rate to be 50% - 60%; Step e, decarburization blowing: After slag discharging is completed, carry out decarburization blowing.
2. The method for improving the dephosphorization capacity in the early stage of converter blowing according to claim 1, characterized in that: In the early stage of converter blowing in step b, the basicity of the slag is controlled to be 1.2 - 2.0, the FeO content is controlled to be 8% - 25%, and the MgO content is controlled to be 4% - 6%.
3. The method for improving the dephosphorization capacity in the early stage of converter blowing according to claim 2, characterized in that: The molar ratio of Mg and Fe in the steel slag emulsifier is 1:
1.
4. The method for improving the dephosphorization capacity in the early stage of converter blowing according to claim 3, characterized in that: The addition rate of the steel slag emulsifier is controlled to be 0.1 - 0.5 kg / t / min.
5. The method for improving the dephosphorization capacity in the early stage of converter blowing according to claim 4, characterized in that: The molten bath temperature is 1350 - 1400 °C when adding the steel slag emulsifier.
6. The method for improving the dephosphorization capacity in the early stage of converter blowing according to claim 5, characterized in that: The steel slag emulsification degree in step c is controlled to be 50% - 80%.
7. The method for improving the dephosphorization capacity in the early stage of converter blowing according to claim 6, characterized in that: During the blowing process in step c, 2 minutes before blowing, control the oxygen lance flow rate to 3.5-4m 3 / min / t, the oxygen lance height is 2-3m above the molten pool liquid surface; within 2-4min of blowing, adjust the oxygen lance flow rate to 3.0-3.3m 3 / min / t, the oxygen lance height is adjusted to 1-1.5m above the molten pool surface.
8. The method for improving the dephosphorization capacity in the early stage of converter blowing according to claim 7, characterized in that: Step e: After the slag discharge is completed, blowing and decarburization are carried out. The oxygen supply intensity during the decarburization period is controlled at 3.3-3.8 Nm 3 / min / t.
9. The method for improving the dephosphorization capacity in the early stage of converter blowing according to claim 8, characterized in that: In step e, the addition amount of lime during the decarburization period is 10 - 30 kg / t, regulate the binary basicity of the decarburization slag in the converter to be 2.5 - 4.0, the MgO content in the slag is 7% - 10%, tap the steel and retain slag after the converter blowing is completed.
Citation Information
Patent Citations
Smelting process for producing ultra-low phosphorous steel by converter
CN101906504A
Converter dephosphorizing and steelmaking method
CN102071277A
Production method of low-sulfur steel
CN102443675A
Process technology method for efficient and low-cost converter production of ultra-low phosphorus liquid steel
CN102618689A
Smelting method of ultra-low phosphorus steel
CN102776314A